LEGAL POLITICS OF PROTECTION OF INDONESIAN TRADITIONAL CULTURAL EXPRESSIONS / FOLKLORE - Kholis Roisah (Diponegoro Law Review, 2017)
This research discusses about the politics of legal protection of traditional cultural expressions/ folklore in Indonesia. It is important to note that the protection of traditional cultural expressions is necessary in order to form a national identity. Protecting traditional cultural expressions legally can also be the indication of civilization in order to force the state to conduct its obligation to develop national culture. The method of approach used in this study was non doctrinal or socio-legal approach. From the result of the research, it is found that first, constitutionally, politics of legal protection of traditional cultural expressions has obliged a state to develop its national culture, guarantee the freedom or independence of all components of the people in preserving and developing the culture and enjoy the product of the culture, in this case including in preserving and developing traditional cultural expressions/folklore. It must also guarantee the collective rights of all components of people including communities of people who preserve traditional cultural expressions for the sake of the wellbeing and the progress of the communities, or to a broader sense for the sake of the wellbeing of all Indonesian people. The second, operationally, politics of protection of traditional cultural expressions gives the state the authority to formulate policies, regulate, administrate, manage, promote and supervise the use of traditional cultural expressions. The state must be able to protect and guarantee all people’s rights related to traditional cultural expressions/folklore and various national cultural properties that can directly enjoy by the people. In addition, the state must also be able to prevent and handle the use of traditional cultural expressions that cause people to lose their access and rights to the traditional cultural expressions.